PENYUSUNAN LAPORAN KEUANGAN BERBASIS APLIKASI AKUNTANSI UKM PADA UMKM KEMPLANG PAK EFFENDI - Hartaty, Sri; Juliyanto, Juliyanto; Choiruddin, Choiruddin; Aprianti, Siska; Faridah, Faridah (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2023)
This writing aims to compile financial reports on UMKM Kemplang Pak Effendi using the UKM Accounting application. The data used were obtained from the company through interviews, observation and documentation studies. Based on the data obtained, UMKM Kemplang Pak Effendi, which is engaged in the manufacture and sale of kemplang, only records cash income and disbursements without preparing financial reports. This SME accounting application aims to assist MSME players in compiling their business financial reports. Based on the results of the writing, the SME Accounting application can help Kemplang Mr. Effendi's MSMEs to compile financial reports. However, the drawback of this application is that the name of the financial report does not match the applicable accounting standards. Keywords: Financial, Report, Android, Application, UMKM